Cell-Specific Vulnerability of Human Glioblastoma and Astrocytoma Cells to Mephedrone—An In Vitro Study - Marta Marszalek-Grabska; Marta Kinga Lemieszek; Michal Chojnacki; Sylwia Winiarczyk; Joanna Jakubowicz-Gil; Barbara Zarzyka; Jarosław Pawelec; Jolanta H. Kotlinska; Wojciech Rzeski; Waldemar A. Turski (Molecules)
Glioblastoma multiforme is a highly aggressive intrinsic brain tumor with a very poor survival rate. The main treatment for cancer is surgery combined with postoperative radiotherapy and temozolomide chemotherapy. Since the outcomes of treatment are unsatisfactory, the search for more effective drugs is crucial. Our previous study indicated that mephedrone, a synthetic cathinone, reduced neuron and astrocyte viability and oligodendrocyte proliferation. The aim of the present study was to investigate the effect of mephedrone on selected human glioblastoma (LN-18, LN-229, T98G) and human anaplastic astrocytoma (MOGGCCM) cell lines. The effects of mephedrone on cell viability and proliferation, DNA synthesis, cell cycle progression and the type of cell death were studied. Our results showed that mephedrone possesses potential anticancer activity. The viability and proliferation of all four human glioblastoma and human anaplastic astrocytoma cell lines used were decreased in a concentration-dependent manner. Studies conducted on LN-18 and T98G cells confirmed the significant antiproliferative properties of mephedrone, which reduced DNA synthesis and affected cell cycle progression. Microscopic evaluation supported the antiproliferative effect of the tested compounds. Moreover, substantial cytoplasmic vacuolization in the LN-18 cell line was revealed. This finding may indicate the potential of mephedrone in anticancer therapy.